Prefazione - Frommel, Sabine (Opus Incertum, 2019)
The international conference "Il Rinascimento delle grotte", which took place the February 22, 2019 in Villa Castello is part of a European programme concerning the origins and evolution of grottoes and nymphaeums in the modern period. The contributions published in this review throw new light on the specific character of the famous grotto degli animali as a technical and artistic masterpiece. They point out the narrow links of narrative, symbolical and mythological meaning serving as an instrument of princely self-representation. Furthermore, they focus on the history of the restorations of the grotto and particularly the recent interventions, which combine survey and diagnostic methods in a new way. On the other hand, there is an increasing interest regarding the influence of Florentine models of the late 16th and early 17th century in France and in Germany. The decoration of grottoes is a favourite subject in the letters of ambitious patrons requesting drawings and materials and even skilful craftsmen from the Grand Duke of Tuscany. So this typology became a significant article of exportation of Florentine culture with a strong impact on European art in the modern period.